Institutional failures and transaction costs of Bulgarian private research institutes - Shteryo Nozharov (ZBW - Leibniz Information Centre for Economics; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The paper analyses the reasons for poor performance of private research institutes in Bulgaria. In this regard the Institutional Economics methods are used. A connection between smart growth policy goals and Bulgarian membership in EU is made. The gaps in the institutional environment are identified as well as measures for their elimination are proposed. The main accent of the study is put on the identification of transaction costs, arisen as a result of the failures of the institutional environment where Bulgarian private research institutes operate. An additional objective of the publication is to identify the cumulative impact of transaction and social costs concerning the same transaction. Special attention is paid to the need of distinguishing the joint effect and at the same times it to be distinguished by the aforementioned factors in order to be taken into account in future econometric researches. A definition of the term “private research institutes” so as to be distinguished from Think-Tank organizations is proposed.
Keywords: E14; O17; 330; Private research institutes; Institutional Economics; Smart growth; Transaction costs